2012
DOI: 10.1108/13552551211268148
|View full text |Cite
|
Sign up to set email alerts
|

The impact of story bound entrepreneurial role models on self‐efficacy and entrepreneurial intention

Abstract: Purpose -The purpose of this paper is to measure the impact of positive and negative same-gender fictional role models on students' self-efficacy and entrepreneurial intention. Design/methodology/approach -The authors conducted an experimental research on 276 French students. Structural equation modeling techniques were employed to measure role model identification, attitude toward the role model, emotional arousal, entrepreneurial self-efficacy and entrepreneurial intention. Findings -Exposure to fictional ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 79 publications
(105 reference statements)
8
100
1
9
Order By: Relevance
“…Results highlight that entrepreneurial feasibility is higher for groups who watched videos. In addition, Laviolette et al (2012) show that observing a fictional role model-'entrepreneurs' testimonials and narratives'-positively influences entrepreneurial self-efficacy and intentions. They find that as long as role models provide the possibility for an individual to identify with them, they can stimulate a positive attitude toward entrepreneurship and increase entrepreneurial activities.…”
Section: Unrelated Models (5 Papers)mentioning
confidence: 93%
See 3 more Smart Citations
“…Results highlight that entrepreneurial feasibility is higher for groups who watched videos. In addition, Laviolette et al (2012) show that observing a fictional role model-'entrepreneurs' testimonials and narratives'-positively influences entrepreneurial self-efficacy and intentions. They find that as long as role models provide the possibility for an individual to identify with them, they can stimulate a positive attitude toward entrepreneurship and increase entrepreneurial activities.…”
Section: Unrelated Models (5 Papers)mentioning
confidence: 93%
“…Moreover, the authors find that stories about successful fictional role models had greater effects compared to stories of unsuccessful 'real-life' role models. Therefore, it has been suggested that telling stories about entrepreneurs be used in entrepreneurship education programs to influence entrepreneurial intentions (Fellnhofer 2017b;Laviolette et al 2012). In this respect, Radu and Loué (2008) suggest that using social media could create a greater impact if it exposes young generations to more similar idealistic (and realistic) role models instead of heroic role models that could fulfill social and/or family requirements.…”
Section: Unrelated Models (5 Papers)mentioning
confidence: 99%
See 2 more Smart Citations
“…From another optic, several scholars have analyzed the relationship between gender and attitudes with new venture creation (Delmar & Davidsson, 2000;Laviolette et al, 2012), and have found that males have a higher preference for entrepreneurship behavior than females. According to Hindle et al (2009), it has been suggested that female entrepreneurs are disadvantaged compared to men with respect to most forms of human capital and also because of a lack of suitable and effective social networks.…”
Section: The Perceived Behavioural Controlmentioning
confidence: 99%